Morgan line and its relationship with distraction index, angle of inclination and degenerative joint disease in the diagnosis of canine hip dysplasia - Miranda,F.G. (2016)
ABSTRACT We evaluated 160 hip joint radiographs of 40 dogs of different large breeds (25 females and 15 males) from the metropolitan area of Belo Horizonte, Minas Gerais, Brazil. The radiographs of each dog were obtained at two different stages: stage 1 (mean 7.23 months) and stage 2 (mean 14.25). The conventional radiographic method (CRM) and the radiographic distraction method (RDM) were used, carried out in both stages. CRM measured the Norberg angle (NA), the angle of inclination (AI) and evaluated the presence of degenerative joint disease (DJD). The MRD was performed to establish the distraction index (DI). The aims were to evaluate the presence of the Morgan line and other signs of DJD and correlate them with the degree of canine hip dysplasia (CHD) and also check if the DI greater than 0.3 (first stage) was associated with the presence of ML (second stage). It was found that DI, AI and changes of femoral neck and the formation of osteophytes were associated with the presence of ML. It was observed that if the DI is greater than 0.3 at the first stage, the chance of a positive outcome of ML in the second stage increases by 7.2 times. Thus, 49 joints showed DI > 0.3 at the first stage, in which 31 (63.3 %) presented ML at the second stage. Of the 31 animals that showed DI ≤ 0.3 at first, six (19.4%) had LM at the second stage. There has been a significant association between the presence of ML and the degree of CHD. The more severe the CHD, the higher the percentage of positive ML results. Thus, among the 24 (60 %) animals that showed ML, 11 (45.83 %) were classified as severe dysplastics, 5 (20.83%) as moderate and 8 (33.33 %) as mild. None of the animals classified as normal or borderline presented ML. Among the 8 animals classified as mild dysplastics, 5 showed only ML as DJD.